Konsep Jiwa, Kesehatan Mental dan Psikoterapi Ibn Zakaria Al-Razi - Rahmawati, Rizkia Amalia; Khudori Soleh, Achmad (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2024)
Ibn Zakaria al-Razi specialized in psychotherapy. His book "Al-Thibb al-Ruhani" serves as a crucial reference for this research. The main objective of this research is to comprehend al-Razi's perspective on the concepts of the soul, mental well-being, and psychotherapy. The research methodology utilized is qualitative, employing a literature review approach. The findings indicate that, according to al-Razi, the human soul comprises three dimensions: the divine soul (al-Nafs an-Nathiqah al-Ilahiyah), the animalistic soul (al-Nafs al-Ghadabiyah), and the vegetative soul (al-Nafs al-Nabatiyah). The divine soul is seen as eternal, akin to God. Al-Razi emphasizes that mental health significantly affects an individual's physical well-being. Moreover, psychological stability is influenced by the surrounding environment. Thus, the healing process for the soul involves both physical and psychological therapy. These therapies are founded on two fundamental principles: (1) the control of intellect over desires (darurah tahakkum al-aql fi al-hawa) and (2) the restraint of desires and passions (qam'u al-hawa wa al-syahwat). Additionally, al-Razi implements two counseling techniques: accepting reality and returning to Allah Swt.